Affirmative Action Attitudes of Whites: Evidence from a List Experiment Survey in Brazil - Vidigal,Robert (2018)
Recently in Brazil, public policies have begun to be implemented to reduce discrimination and promote the inclusion of excluded social groups based on a specific individual characteristic: race. However, there is little public consensus about such policies, especially among whites. In this work, I look at the racial attitudes towards affirmative action among white college students. I make use of new research methods for the empirical study of socially sensitive issues and ask whether these attitudes stem from prejudice, conflicts between social groups or individual political predispositions. Furthermore, I ask what is the relationship between political knowledge and such racial attitudes. I use the list experiment method because of its potential to offset the under-representation of opinions and attitudes. This approach allows respondents to be indirectly questioned, ensuring greater sincerity in their answers and, hence, providing more accurate portrayal of attitudes. This study shows that white respondents’ answers on affirmative action policies are strongly affected by social desirability. Only 6% of white respondents agreed that it is important to have a quota policy for blacks at the Federal University of Santa Catarina (UFSC). Individuals with greater political knowledge tend to express greater support for affirmative action and hold more coherent racial attitudes Results also reveal that negative racial attitudes and political predispositions are both determinants of the white student’s attitudes towards affirmative action policies.